Rational Choice Theory in the Study of Folk Beliefs (The Case of Yiey Mao Belief among the Khmer People in Southern Vietnam) - NGO, An Thanh (Journal of Ecohumanism, 2025)
Folk beliefs play a crucial role in shaping the spiritual, social, and economic lives of communities. Among the Khmer people in Southern Vietnam, the Yiey Mao belief represents a unique cultural-religious phenomenon that has persisted despite modernization and social changes. This study applies Rational Choice Theory (RCT) to examine why the Khmer people continue to practice and maintain the Yiey Mao belief. RCT posits that individuals make decisions based on rational calculations to maximize their perceived benefits. Through an analysis of economic, social, and political factors, this study argues that the worship of Yiey Mao is a rational choice influenced by both tangible and intangible benefits. Economically, rituals associated with Yiey Mao contribute to spiritual tourism and community-based economic activities. Socially, participation in these rituals strengthens social capital, fostering community cohesion and reinforcing Khmer cultural identity. Politically, the belief system provides a mechanism for leadership and social influence within the community. However, this study also acknowledges the limitations of RCT in fully explaining the persistence of the Yiey Mao belief. Factors such as tradition, emotions, and cultural identity play a significant role in religious decision-making, sometimes overriding purely rational calculations. As modernization continues to impact Khmer society, this research highlights the adaptability and transformation of folk beliefs, suggesting that future studies should incorporate interdisciplinary approaches to better understand the dynamics of religious practices in contemporary contexts.